2002
DOI: 10.1089/108497802760363178
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Induced by Culturing MH134 Cells in the Presence of Porcine Skin Gelatin In Vitro

Abstract: Porcine skin (PS) gelatin showed antitumor effect in vitro on MH134 murine hepatoma cells. We analyzed the effect of PS gelatin on MH134 cells compared to the effect of Bovine bone (BB) gelatin, 5-Fluorouracil (5-FU) and 7-ethyl-10-hydroxycamptothecin (SN-38). We previously suggested that PS gelatin induces apoptosis in MH134 cells using flow cytometric analysis. We performed agarose gel electrophoresis and electron microscopic studies to ascertain apoptosis. Agarose gel electrophoresis showed the typical DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Ito et al [8] demonstrated in vitro that porcine skin (PS) gelatine induced apoptosis in MH134 cells evaluated through flow cytometry, agarose gel electrophoresis and electron microscopy. On the other hand, bovine bone (BB) gelatine did not induce apoptosis or necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ito et al [8] demonstrated in vitro that porcine skin (PS) gelatine induced apoptosis in MH134 cells evaluated through flow cytometry, agarose gel electrophoresis and electron microscopy. On the other hand, bovine bone (BB) gelatine did not induce apoptosis or necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, bovine bone (BB) gelatine did not induce apoptosis or necrosis. Probably, these differences resulted from different primary sequence of amino acids in these collagen molecules [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations